CASCA DE ARROZ COMO ADSORVENTE PARA ÍONS DE METAIS PESADOS: Caracterização e modificação química - Penha, Rosiane Silva (2009)
Adsorption of some metal ions (Co2+, Ni2+, Cu2+ e Zn2+) from aqueous solutions (pH 5.0) onto in nature rice husk (0.088 <  < 0.177 mm) was investigated. All experiments were conducted by the batch adsorption techniques at room temperature (28  1°C) and under constant stirring. The adsorption amounts were determined using atomic absorption spectroscopy. The Adsorption data were studied using two well-known adsorption models: Langmuir and Freundlich. The results showed that the metal ions uptake processes mediated by rice husks were fitted Freundlich isotherm model, suggesting that all adsorptions are governed by weak electrostatic interactions. According to the equilibrium studies, the selectivity sequence can be given as: Ni2+ (0.08 mmol g-1) < Co2+ (0.16 mmol g-1) < Zn2+ (0.40 mmol g-1) < Cu2+ (0.89 mmol g-1). This result showed that natural rice rusk holds good potential to remove such metal ions from wastewater. The effect of chemical pretreatment of rice husk on adsorption was also investigated. In nature rice husk (IN) was pretreated with phosphoric acid (AF); phosphoric acid and urea (AFU) and sodium metaperiodate (MP). AFU was the best adsorbent for all metal ions investigated [Ni2+ (0,96 mmol g-1) < Cu2+ (1,20 mmol g-1) < Co2+ (1,59 mmol g-1) < Zn2+(1,80 mmol g-1)]. In addition, in nature rice husk was characterized by chemical-bromatological analyses (humidity, ash, protein, carbohydrate, starch, lipid and fibers), scanning electron microscopy, solid-state 13C NMR and specific BET surface area. Some properties of in nature and pretreated samples were studied by infrared spectroscopy, thermogravimetric analysis, X-ray diffractometry, and elemental analyses. The results showed only marginal changes among them.